Application of improved graph convolutional networks in daily-ahead carbon emission prediction - Pan, Feng; Yang, Yuyao; Ji, Yilin; Li, Jinli; Zhang, Jun; Zhong, Lihua (Frontiers in Energy Research, 2024)
With the increasing complexity of power systems and the proliferation of renewable energy sources, the task of calculating carbon emissions has become increasingly challenging. To address these challenges, we developed a new method for predicting carbon emission factors. Bayesian Optimization Techniques Graphical Convolutional Networks with long-and short-term network (BO-TGNN) is used to predict the carbon emissions of the power system.The method aims to quickly predict the day-ahead carbon emissions of power system nodes with enhanced feature extraction and optimized network training hyperparameters. The effectiveness of the proposed method is demonstrated through simulation tests on three different power systems using four deep learning algorithms. The method provides a tailored solution to the evolving needs of carbon reduction efforts and is a significant step forward in addressing the complexity of carbon emission calculations for modern power systems.